Game Laboratory Usage Model for Game Development and Simulation Projects - Agung Riyadi; Riwinoto Riwinoto (Politeknik Negeri Batam, 2020)
The use of laboratories in indonesia’s universities are usually only used as a means of learning for teaching activity. Unlike the use of europe’s laboratories, not only a means of supporting teaching, but can also be used for research, project development, training and others. Therefore, this study try to applied laboratory models that can be used not only for teaching activity. In this study, 4 models were applied for laboratory use including Teaching Models, Project Models, Evaluation Models and Research Models. The results obtained from the application of this model are the existence of mapping and learning models for courses that support each other in producing game development projects, and the results of evaluations of game development that can be used as research. With this, the use of a game laboratory can be more optimal.